Potencial energético de resíduos de usinas sucroalcooleiras na região de Ilha Solteira, SP - Alves, Luiz Henrique Carneiro [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The use of non-renewable energy has been causing environmental problems to planet Earth for years and, to maintain the inevitable need for electricity, it is necessary to search for renewable alternatives less harmful to the environment. Brazil, for having a considerable continental area, climatic diversity and consolidated energy production ventures, become advantageous for generating renewable energy. A great source of renewable energy is sugarcane biomass, a crop that is very well adapted to different regions and extensions of the country, including the study area, as it is suitable for regions with a long, hot and high season. incidence of radiation, making Brazil the world leader in its production. This work elucidates, through mathematical models and quantitative analyses, the Brazilian renewable energy matrix by the sugarcane biomass and its potential in participation in the electricity demand by Brazilians, mitigating the environmental impacts arising from the production of energy and presented itself as a potentiating source to meet both needs. Using the website of the União Nacional de Bioenergia (UDOP) and the MAPS tool, from google, the sugarcane units in the region of 200 km from Ilha Solteira were identified so that contact could be made for the analysis of the energy potential of this segment. With the need for environmental, social and economic improvements, in addition to the deficit of hydraulic levels in hydroelectric plants, a matrix with high participation in the generation of Brazilian energy, the cogeneration of energy by sugarcane biomass can present itself with greater participation for the energy sector.

O uso de energias não renováveis causa problemas ambientais ao planeta Terra há anos e, para manter a inevitável necessidade de energia elétrica, faz-se necessário a busca de alternativas renováveis que sejam menos nocivas ao meio ambiente. O Brasil, por possuir uma considerável área continental, diversidade climática e empreendimentos de produção de energia consolidados, se torna vantajoso para a geração de energia renovavél. Uma ótima fonte de energia renovável é a da biomassa da cana-de-açúcar, uma cultura muito bem adaptada em diversas regiões e extensões do país, inclusive a da área de estudo, por ser propícia a regioes com estação longa, quente e com alta incidencia de radiação, tornando o Brasil líder mundial em sua produção. O presente trabalho tem como finalidade elucidar, por modelos matemáticos e analises quantitativas, a matriz energética renovável brasileira pela biomassa da cana-de-açúcar e sua potencialidade em participação na demanda de eletricidade pelos brasileiros, mitigando os impactos ambientais proveniente na produção de energias e apresentado-se como fonte pontencializadora para atender ambas necessidades. Utilizando o site da União Nacional de Bioenergia (UDOP) e a ferramenta MAPS, do google, foi identificado as unidades sucroalcooleiras na região de 200 km de Ilha Solteira para que pudesse ser feito contato para a análise da potencialidade energética desse seguimento. Com a necessidade de melhorias ambientais, sociais e econômicas, além do défice dos níveis hidráulicos em hidrelétricas, matriz com alta participação na geração da energia brasileira, a cogeração de energia por biomassa da cana pode se apresentar com maior participação para o setor energético.
Energy potential of residues from sugar and ethanol plants in the region of Ilha Solteira, SP
Keywords: Biomass; Energy matrix; Renewable energy; Sugar cane; Biomassa; Cana-de-açúcar; Energia renovável; Matriz energética